2022
DOI: 10.4251/wjgo.v14.i7.1324
|View full text |Cite
|
Sign up to set email alerts
|

Effect of obesity on post-operative outcomes following colorectal cancer surgery

Abstract: BACKGROUND Colorectal cancer (CRC) resection is currently being undertaken in an increasing number of obese patients. Existing studies have yet to reach a consensus as to whether obesity affects post-operative outcomes following CRC surgery. AIM To evaluate the post-operative outcomes of obese patients following CRC resection, as well as to determine the post-operative outcomes of obese patients in the subgroup undergoing laparoscopic surgery. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…This is because obesity is an independent risk factor for postoperative complications following laparoscopic right hemicolectomy [ 40 ]. Additionally, obesity (BMI > 30.0 kg/m 2 ) is associated with increased cardiovascular burden, respiratory complications, as well as higher rates of conversion to open surgery and postoperative complications [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is because obesity is an independent risk factor for postoperative complications following laparoscopic right hemicolectomy [ 40 ]. Additionally, obesity (BMI > 30.0 kg/m 2 ) is associated with increased cardiovascular burden, respiratory complications, as well as higher rates of conversion to open surgery and postoperative complications [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that a higher BMI predicts worse outcomes in colorectal surgery [13,14]. This is attributed to both the increased technical challenges as well as associated physiological alterations leading to increased intraoperative and postoperative complications [15][16][17][18]. Despite the improved operative and anaesthetic techniques, some controversy still exists as to whether MIS leads to similar improvements in outcomes in the obese patient population as in the nonobese population [15,16,19].…”
Section: Introductionmentioning
confidence: 99%